Global Communication Competence: a Framework of Intercultural Skills Development in Sport and Tourism Higher Education - Lukianets, Halyna; Lukianets, Tetiana (Physical Education Theory and Methodology, 2020)
Purpose. The research aims at multi-faceted study of global communication competence, which is a vital soft skill for professional development of students, acquiring their degrees in sport and tourism. Materials and methods. Qualitative research methods applied in the research include theoretical analysis of relevant scientific findings, synthesis and modelling, pedagogical observation and evaluation. Quantitative analysis relates to questioning and data processing, in particular, 50-question Intercultural Quiz, conducted among 352 students of NUUPES and NUFT. Results. The conducted research of global communication competence of the first and fifth year university sport and tourism students shows clear correlation between the level of education and gained global communication expertise, presented by the communicative skills of critical thinking and cooperation. The analysis of statistic data has proved that along with improved self-awareness, disciplines more than doubled students’ global communication competence within five academic years. In addition to quantitative improvement, the quality of the intercultural communication is enhanced, as essential professional skills are gained in the sphere of students’ future occupation. Professional orientation of global communication competence outlines sportive and medical inclination of NUUPES students’ higher education, and tourism and hospitality focus of NUFT students’ training. Conclusions. The results of the study have proven that contemporary university students who get degrees in the fields of sport and tourism perceive culturally-bound information when attending their on-line and off-line academic courses and participating in various multicultural events in and outside university setting. In this way they acquire attitudes and values of self-awareness and recognition of ethnical diversity. Established values transform into production and result in implementation of culturally aware behaviour, represented by a high level of self-evaluation and persuasion abilities directed to effective, yet tolerant way of problem solving and shared responsibility.